The Effectiveness of the Affordable Market Program in Improving Community Purchasing Power in Palu City - Fitri Indriani; Muhtar Lutfi (Studi Ilmu Manajemen dan Organisasi, 2026)
Purpose: This study investigates the effectiveness of the Cheap Market Program initiated by the Trade and Industry Office of Palu City in enhancing the purchasing power of lower-middle-income communities. The program acts as a local government intervention to control the rise in basic commodity prices, especially during festive seasons and economic instability. Methodology/approach: A qualitative descriptive approach was used, involving data collection through observation, interviews, documentation, and a Likert-scale questionnaire. The instrument was based on Campbell’s five indicators of effectiveness and distributed to 30 program beneficiaries. Results/findings: The program was found to positively influence household purchasing power, particularly by offering affordable prices and ensuring staple goods availability. 63.3% of respondents rated the program as very effective, and 36.7% as effective. However, implementation challenges remain, including limited stock, long queues, and uneven information dissemination. Conclusion: The Affordable Market Program in Palu City is effective in improving community purchasing power by providing subsidized essential goods. Despite limitations in coverage and resources, the program delivers meaningful economic benefits and should be sustained with improved targeting and coordination. Limitations: The study is context-specific to Palu City and involves a limited number of respondents, thus restricting generalizability and statistical inference. Contribution: The study contributes to the discourse on local government social welfare initiatives by providing empirical evidence of program effectiveness and offering recommendations to improve policy design and implementation.